A DISTRIBUTED HYBRID MODEL OF SOLAR-WIND-SMALL HYDRO FOR POWER GENERATION SYSTEM - Bahel, Shammi; Singh, Harinder (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Renewable energy technologies offer the promise of clean, abundant energy gathered from self-renewing resources such as the sun, wind, water, earth, and plants. In this thesis a detailed modeling of hybrid power generation system of solar, wind and small hydro has been developed in Matlab. The simulation includes all realistic components of the system. In this thesis, the power delivered by the combine system component is compa red with each other and various conclusions are drawn. We have proposed a model of 5MW that contains 3MW of small hydro plant, 1 MW of solar plant and 1 MW of wind plant. We have prepared a cost analysis report that indicates it is profitable to go for such model as it satisfies our current and future energy demands. Moreover the electricity generated by the proposed model is available at a very lesser rate as compared to our current electricity tariff rates.